Stakeholders' information needs for sustaining waqf: development of theoretical framework - Baharin, NorBahriah; Siraj, Siti Alawiah; Mohd Ariffin, Noraini; Osman@Hussin, Ahmad Zamri (Intelligentia Resources, 2023)
Waqf has become a pivotal social welfare sector which provides socioeconomic sustainability. In this light, it required a comprehensive framework to effectively incorporate stakeholders’ needs and accounts for sustainability to improve transparency and accountability. This research paper endeavours to bridge the current research gap by proposing a novel framework for waqf information disclosures, drawing on insights from stakeholder theory and accounting for sustainability. The study reviews existing literature on stakeholder theory and empirical studies using a conceptual approach to build a solid theoretical foundation. This study suggests using the stakeholder salience model by Mitchell, Angle, and Wood (MAW) Model (1997) to ascertain stakeholders' attributability and influence in developing comprehensive accounting for sustaining waqf usufruct. By highlighting the roles of "Stakeholders" and "Accounting for Sustainability", this framework aims to empower waqf institutions in meeting stakeholders' diverse needs and expectations. It is asserted that understanding the stakeholders' influence and attributes can contribute to the sustainability of organisations through comprehensive information disclosure in accounting to the stakeholders. By bridging the gap between stakeholders' expectations and information needs, waqf institutions can cultivate a more resilient and dynamic platform for enhancing socioeconomic benefits through strengthening accountability and transparency for sustainability in waqf. This paper also provides an opportunity for further empirical studies to prove that information disclosures may influence and be attributable to stakeholders’ roles in sustaining organisations' benefits. This paper also guides future conceptual and empirical investigations of other factors influencing waqf sustainability.